Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Progress on the addition of exogenous lipids to surimi: A review - Li Yuan; Mingfeng Xu; Abdul Razak Monto; Wengang Jin; Nannan Zhou; Zhiyu Xiong; Tong Shi; Ruichang Gao (Food Chemistry, 2026)

Succession patterns, environmental connections, and assembly mechanisms of gut microbiota in the giant freshwater prawn (Macrobrachium rosenbergii) across lifespan - Songbao Zou; Yao Zheng; Julin Yuan; Meng Ni; Mei Liu; Dan Zhou; Qiang Gao; Mingfeng Deng; Ruichen Wang; Xin Zhang (Aquaculture, 2026)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Influence of aromatics on the hydrodesulfurization reaction pathway of the NiMo/Al2O3 catalyst using quasi-in situ characterization techniques - Longxin Gao; Wenhui He; Weiming Zhai; Mudi Xin; Wei Wang; Yanjuan Xiang; Hui Yuan; Sa Wang; Feng Liu; Guangtong Xu; Limei Qiu; Mingfeng Li (Fuel, 2025)

Single-step synthesis of nitrogen and phosphorus co-doped biochar and its application in dye removal: synergistic effects of adsorption and peroxymonosulfate activation - Yixuan Shi; Mingfeng Yin; Dong Liu; Xingrui Gao; Xiao Liu; Tengteng Yang; Zuoping Zhao; Xiaohui Ji; Caibin Zhao; Xianzhao Shao (Environmental Research, 2025)

New insights into the remediation of chromium-contaminated industrial electroplating wastewater by an innovative nano-modified biochar derived from spent mushroom substrate: Mechanisms, batch study, stability and application - Jingyi Wang; Yongduo Guan; Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Chemosphere, 2024)

Efficient chromium remediation using eco-innovative biochar in a novel two-stage upflow fixed bed system - Jingyi Wang; Yongduo Guan; Jiahui Fu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Journal of Water Process Engineering, 2024)

Screening of saline-alkali tolerant microorganisms and their promoting effects on rice growth under saline-alkali stress - Jiahui Fu; Yawen Liu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Journal of Cleaner Production, 2024)

Separation of spring viraemia of carp virus from large-volume samples using immunomagnetic beads - Jing Hongli; Zhang Min; Gao Longying; Si Liegang; Wang Na; Ge Mingfeng; Xu Shengwei; Wang Jianping; Wu Shaoqiang (Archives of Virology, 2024)

Performance Comparison of Sea Cucumber Detection by the Yolov5 and DETR Approach - Xin Yuan; Shutong Fang; Ning Li; Qiansheng Ma; Ziheng Wang; Mingfeng Gao; Pingpeng Tang; Changli Yu; Yihan Wang; José-Fernán Martínez Ortega (Journal of Marine Science and Engineering, 2023)
Sea cucumber detection represents an important step in underwater environmental perception, which is an indispensable part of the intelligent subsea fishing system. However, water turbidity decreases the clarity of underwater images, presenting a challenge to vision-based underwater target detection. Therefore, accurate, real-time, and lightweight detection models are required. First of all, the development of subsea target detection is summarized in this present work. Object detection methods based on deep learning including YOLOv5 and DETR, which are, respectively, examples of one-stage and anchor-free object detection approaches, have been increasingly applied in underwater detection scenarios. Based on the state-of-the-art underwater sea cucumber detection methods and aiming to provide a reference for practical subsea identification, adjacent and overlapping sea cucumber detection based on YOLOv5 and DETR are investigated and compared in detail. For each approach, the detection experiment is carried out on the derived dataset, which consists of a wide variety of sea cucumber sample images. Experiments demonstrate that YOLOv5 surpasses DETR in low computing consumption and high precision, particularly in the detection of small and dense features. Nevertheless, DETR exhibits rapid development and holds promising prospects in underwater object detection applications, owing to its relatively simple architecture and ingenious attention mechanism.

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Effects of frequencies on the cyclic behavior of marine soft clay under different consolidated stress paths - Mingfeng Li; Ming Dai; Shengnan Yao; Shihu Gao; Guohui Yuan (Marine Georesources & Geotechnology, 2023)

SERS “hot spot” enhance-array assay for misfolded SOD1 correlated with white matter lesions and aging - Feng Gao; Jingyi Sun; Minmin Yao; Yanan Song; Hui Yi; Mingfeng Yang; Qingbin Ni; Jiming Kong; Hui Yuan; Baoliang Sun; Ying Wang (Analytica Chimica Acta, 2023)

Post-cyclic undrained shear behavior of soft marine clay under anisotropic consolidation stress paths - Ming Dai; Xiaobing Li; Ziyang Gao; Mingfeng Li (Marine Georesources & Geotechnology, 2022)

The optimal combination form of vacuum pre-loading combined with electro-osmosis and with dynamic compaction method on the improvement of dredged slurry - Xiuqing Hu; Ziyang Gao; Feiyu Liu; Yu Tao; Donghai Xu; Yunguo Du; Changfei Gou; Mingfeng Li (Marine Georesources & Geotechnology, 2021)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)

Identification of Prognostic Signatures of Alternative Splicing in Glioma - Yu Zeng; Peidong Zhang; Xizhao Wang; Ke Wang; Mingfeng Zhou; Hao Long; Jie Lin; Zhiyong Wu; Liang Gao; Ye Song (Journal of Molecular Neuroscience, 2020)

Construction of a series of episomal plasmids and their application in the development of an efficient CRISPR/Cas9 system in Pichia pastoris - Yang Gu; Jucan Gao; Mingfeng Cao; Chang Dong; Jiazhang Lian; Lei Huang; Jin Cai; Zhinan Xu (World Journal of Microbiology and Biotechnology, 2019)

Toward Improved Calibration of SWAT Using Season-Based Multi-Objective Optimization: a Case Study in the Jinjiang Basin in Southeastern China - Ying Chen; Xingwei Chen; Chong-Yu Xu; Mingfeng Zhang; Meibing Liu; Lu Gao (Water Resources Management, 2018)

Induction and Characterization of Adventitious Roots Directly from the Explants of Panax notoginseng - Xianfu Gao; Chunbao Zhu; Wei Jia; Wenyuan Gao; Mingfeng Qiu; Yongyu Zhang; Peigen Xiao (Biotechnology Letters, 2005)